ANALISIS KARAKTERISASI BETON BERAT MENGGUNAKAN PASIR BESI SEBAGAI PERISAI RADIASI NUKLIR - Endang Haryati; Khaeriah Dahlan (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
A study was conducted to determine and analyze the physical properties of heavy concrete and determine the coefficient of linear absorption of nuclear radiation shielding materials. Methods used in this study is experimental method in the laboratory by making heavy concrete model using a mixture of iron sand in various thicknesses, and then tested for its ability as a radiation shield. The results showed that the weight of concrete using mixture of iron sands produced a compressive strength value of 40.67 MPa, or greater than the weight of concrete without using iron sand which is 20.38 MPa. Coefficient of absorption of heavy concrete materials with iron sand mixture is 0.026 cm, while the heavy concrete without iron sand mixture only has a coefficient of 0.013 cm. HVT values ​​for heavy concrete with iron sand mixture is 26.65 cm, smaller than the concrete without iron sand mixture that is worth up to 53.3 cm. In conclusion, the ability of heavy concrete that uses a mixture of iron sand is better if compared with the nuclear radiation shield from concrete without iron sand. Keywords: Heavy concrete, iron sand, nuclear radiation shield.